Effectiveness of β-lactam and Macrolide Antibiotic Combination in Patients with Community-Acquired Pneumonia: A Review - Hikmah, Nurul; Sholih, Mally Ghinan (Jurnal Pijar Mipa, 2025)
Community-acquired pneumonia (CAP) is a clinically significant lung infection and a leading cause of infectious disease-related death, especially in patients with high-risk factors. This study aims to analyze the effectiveness of a combination of β-lactam and macrolide antibiotics in the treatment of CAP and its impact on reducing mortality. Using the Systematic Literature Review method from sources such as Google Scholar, PubMed, and ScienceDirect, 10 national and international journals were reviewed to evaluate the effectiveness of this combination compared to monotherapy and other combination options. Results showed that the combination of β-lactams and macrolides is effective in improving clinical outcomes, accelerating recovery, and reducing mortality in CAP patients, especially against atypical pathogens that are often not fully treated with β-lactam monotherapy. Factors such as seasonal variations and the patient's state of health also influence the response to this therapy. The most commonly used antibiotics in this combination are Ceftriaxone or Ampicillin/Sulbactam as β-lactams, paired with Azithromycin or Clarithromycin as macrolides.  Therefore, the combination of β-lactams and macrolides is considered an effective primary therapy option for CAP, in accordance with the national guidelines for medical services in Indonesia, which allows flexibility in treatment according to the clinical condition of the patient and the characteristics of the pathogen present.